THE - Handayani, Lilik; Ngadiman, Agustinus (JET ADI BUANA, 2017)
This ex post facto study examines the correlation and theeffectiveness of the language learning strategies on engineering studentsÃ¢â‚¬Ëœlistening comprehension. Further, it strives to figure out the most effectivelearning strategies in improving their listening comprehension. They wereasked to answer both Strategy Inventory for Language LearningQuestionnaire (Oxford, 1990) and ESP Listening Comprehension Test asthe research instruments. The data findings were then classified andanalyzed by applying statistical analysis including Correlational Analysis,Analysis of Variance (ANOVA) and TukeyÃ¢â‚¬Ëœs HSD test. The researchfindings bring to light the correlation between language learning strategiesand engineering studentsÃ¢â‚¬Ëœ listening comprehension. The highestcorrelation can be gained by compensation strategy (with correlation value0,16) and cognitive strategy group (with correlation value -0,14).Meanwhile, the effectiveness of diverse learning strategies on engineeringstudentsÃ¢â‚¬Ëœ listening comprehension has been proven through ANOVAcalculation (F-ratio 2,85 higher than F table 2,00 and p-value 0,007 less than ÃÂ 0.05). A combined metacognitive and affective strategy is revealedas the most effective learning strategy to improve engineering studentsÃ¢â‚¬Ëœlistening comprehension. As a pedagogical implication, English teachersshould encourage the development of ESP learnersÃ¢â‚¬Ëœ awareness of learningstrategies and affection for L2 listening as the first possible keys to success in ESP learning.